The integration of environmental aspects in computer aided molecular design framework - Ooi, Jecksin (2019)
Chemical product design is the process of identifying optimal products for specific applications based on customer needs. This process is often done by Computer Aided Molecular Design (CAMD) technique, a powerful tool to determine molecular structures that meet targeted properties using property prediction models. Most of the CAMD problems focused on designing molecules with desirable physicochemical properties without considering the environmental aspects of molecules during the decision-making stage. However, chemical products with good functionalities do not imply that they are environmental friendly. Hence, besides physicochemical properties, it was also important to consider environmental properties of molecules as design criteria.